The role of the physical education environment in revealing manifestations of social isolation among sixth-grade elementary school students - الشريف, أ. د. حسن هادي صالح; Al-Kufi, Hassanein Abdel Amir Ta'meh (Sulaimani Journal for Humanities, 2025)
Physical education is a rich educational environment filled with dynamic activities that reflect diverse patterns of social interaction among students, making it a fertile ground for identifying social withdrawal or isolation behaviors. This research aims to demonstrate the role of the physical education environment in revealing manifestations of social isolation among sixth-grade students. The researchers employed a descriptive-analytical approach, deemed most suitable for the nature of the research, and utilized a tool specifically designed for this purpose: the "Social Isolation in the Physical Environment Scale," consisting of 35 situational items.The sample comprised the entire research population of 92 students at Al-Abbas Bin Abdul-Muttalib Primary School for Boys in Najaf Governorate/Kufa District. Data were analyzed using appropriate statistical methods. The results showed that the physical environment is an effective means of identifying indicators of social isolation through behaviors such as hesitation, withdrawal, or lack of initiative. Furthermore, high levels of interaction within physical activity were found to be associated with lower manifestations of social isolation. The researchers recommend the need to utilize the kinetic environment as a diagnostic educational tool, and to train teachers to monitor behavioral indicators that may indicate social isolation among students.
Keywords: The physical environment; physical education; social isolation; sixth grade of primary school; social behavior; group interaction